Why White, Not Keynes? : Inventing the Post-War International Monetary System - Boughton, James (IMF Working Papers; Working Paper ;, 2002)
The international monetary system is largely the product of negotiations during World War II between U.S. and U.K. officials, led respectively by Harry Dexter White and John Maynard Keynes. The design of the system, especially the International Monetary Fund, reflects the U.S. plan much more than the British. That outcome resulted not only from the superior economic position of the United States but also from differences between White's and Keynes's views on key issues. Examination of White's economic papers shows that he was more multilateral than Keynes and placed a higher priority on monetary discipline.